Consistency of property income - Pau Gayà Riera; Andreas Hertkorn; Enrico Infante; Balint Murai; Orestis Tsigkas; Leonor Zubimendi (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2022)
This article aims at presenting a tool to identify issues to improve the consistency of the financial and non-financial accounts by institutional sectors. The international statistical standards clearly relate property income and financial assets categories. It is thus possible to derive implicit rates of return, in other words property income in relation to the respective financial position. Implicit returns are calculated to compare the data across institutional sectors and EU Member States with a metric that is intuitive to compilers and users of sector accounts. For Member States, three broad categories of property income are analysed: (i) interest, (ii) return on equity (dividends, withdrawals ...) (iii) other property income (from insurance, pensions investment funds...) and the related financial positions. Implicit rates of return were compiled using the most detailed national data of the October 2020 vintage. Most of the observed variations across sectors and Member States are assessed as largely plausible. However, some observed differences necessitate further analysis for specific resident sectors, as well as for the positions in relation to the rest of the world. Summarising, the results are fairly plausible for implicit interest rates and implicit rate of returns for other property income, and Member State differences are limited. For the implicit return on equity, large cross-Member State differences still exist. The outliers are particularly large for non-financial corporations liabilities and for household assets. Equity issued by non- financial corporations and held by households is largely in the form of unlisted shares and other equity, which makes the recording of the financial positions as well as the respective property income more difficult than for listed shares. Another important result is that the data show no major differences between annual and quarterly rates for implicit interest, return on equity and return on other property income. Structural and repetitive significant inconsistencies across different income type variables and sectors were only observed for few Member States.
Keywords: C82; E01; G20; 330; national accounts; sector accounts; statistical practices